Current status of the Food Security system in Mongolia new policies, and expected outcomes - Deleg, Enkhmaa; Nergui, Sugar; Jambal, Tuyatsetseg; Batbold, Enkhtaivan; Avidsuren, Amarjargal (Proceedings of the Mongolian Academy of Sciences, 2024)
The national food security system in our country is not established well and continues to remain weak. Failures within the system have caused malfunctions and distortions in government policy implementation, leading to unexpected policy shifts. These faults are the main causes of time loss, inter-agency misunderstandings, lack of coordination, information flow deficiencies, and a shortage of skilled human resources. These issues can have a negative impact on food security in Mongolia, resulting in the shortfall of government policy implementation. Coordination of food security activities among government organizations in Mongolia has been unsatisfactory due to the weak system. Government services have not adequately reached organizations at the middle and primary levels in the Mongolian rural provinces. This research paper aims to evaluate the national food security situation based on policies in Mongolia's food sector over the past decade, their implementation, encountered problems, and involved stakeholders. The research findings show that our country's food security system is not well-established, leading to compromised food security, highlighting the urgent need for developing necessary legal and policy documents to effectively implement state food security policy.